Utilisation of sexual and reproductive health services among street children and young adults in Kampala, Uganda: does migration matter? - Mulekya F. Bwambale; Paul Bukuluki; Cheryl A. Moyer; Bart H. W. Van den Borne (BMC, 2021)
Abstract Background While the nexus of migration and health outcomes is well acknowledged, the effect of rural-urban migration on the use of sexual and reproductive health (SRH) services has received less attention. We assessed the effect of rural-urban migration on the use of SRH services, while controlling for confounding, and whether there is a difference in the use of SRH services among migrant and non-migrant street children and young adults. Methods Data were collected from 513 street children and young adults aged 12-24 years, using venue-based time-space sampling (VBTS). We performed multivariate logistic regression analysis using Stata 16.0 to identify factors associated with SRH services use, with rural-urban migration status as the main predictor. Participants were further classified as new migrants (≤ 2 years of stay in city), established migrants (> 2 years of stay in city) or non-migrants (lifelong native street children) with no rural-urban migration history. Results Overall, 18.13% of the street children and young adults had used contraception/family planning, 58.67% had tested for human immunodeficiency virus (HIV) and knew their status and 34.70% had been screened for sexually transmitted infections (STIs). Non-migrants were 2.70 times more likely to use SRH services (HIV testing, STI screening and family planning) compared to the migrants (aOR = 2.70, 95% CI 1.23-5.97). Other factors associated with SRH services use among street children and young adults include age (aOR = 4.70, 95% CI 2.87-7.68), schooling status (aOR = 0.33, 95% CI 0.15-0.76), knowledge of place of care (aOR = 2.71, 95% CI 1.64-4.46) and access to SRH information (aOR = 3.23, 95% CI 2.00-5.24). Conclusions SRH services utilisation among migrant street children and young adults is low compared to their non-migrant counterparts and is independently associated with migration status, age, schooling status, knowledge of place of care and access to SRH information. Our findings call for the need to design and implement multi-dimensional interventions to increase the use of SRH services among street children and young adults, while taking into consideration their migration patterns.